PERAN SOSIAL EKONOMI DALAM MEMODERASI PENGARUH POLA ASUH ORANG TUA DAN TEMAN SEBAYA TERHADAP KARAKTER SISWA - siti hardian; Agus Wahyudin; purwadi suhandini (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The purpose of this study was to analyze 1) Effect of parenting style on the students’ character. 2) Effect of peers on the students’ character. 3) Role of family’s social economic in moderating the influence of parenting style on students’ character. 4) Role of family’s social economic in moderating the influence of peers on students’ character. This research is a quantitative research. Population of this study were all fifth-grade students of SDN Liliriaja District. The sampling technique used cluster random sampling technique with two stage random sampling. Methods in collecting data are questionnaires and documentation. The results of this study are 1) Parenting style has a significant effect on students’ character by 75.7%. 2) Peers has a significant effect on students’ character by 79.8%. 3) Social economy doesn’t has a significant role in moderating the effect of parenting style on students’ character. 4) Social economy has a role in moderating the influence of peers on students’ character by 81%. Thus, to shape good character of students, parents must apply appropriate parenting styles to students, and supervise students in the association of their peers, so they are not influenced by bad peers that will affect the character of students.